Analisis Rasio Keuangan dan Makro Ekonomi Untuk Memprediksi Kondisi Financial Distress Perusahaan Subsektor Makanan & Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Febriani Kala’ (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the effect of financial and macroeconomic ratios on the company's financial distress. In this study, the financial ratios used are the liquidity ratio with the proxy current ratio (CR), the leverage ratio with the proxy debt to assets ratio (DAR), and the profitability ratio with the proxy for return on assets (ROA). Meanwhile, the macro economy is measured by inflation and interest rates. The sample in this study is the food & beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used purposive sampling and obtained 17 companies with 5 years of observation so that there were 85 total observations. The analytical method used is logistic regression analysis using the SPSS version 23 program. The results show that the leverage ratio (DAR) has a positive and significant effect on financial distress, the profitability ratio (ROA) has a negative and significant effect on financial distress, while the liquidity ratio (CR) and macroeconomics as measured by inflation and interest rates have a positive but insignificant effect. against financial distress.